2008
DOI: 10.1210/jc.2008-0352
|View full text |Cite
|
Sign up to set email alerts
|

Iodine Prophylaxis Using Iodized Salt and Risk of Maternal Thyroid Failure in Conditions of Mild Iodine Deficiency

Abstract: Prolonged iodized salt significantly improves maternal thyroid economy and reduces the risk of maternal thyroid insufficiency during gestation, probably because of a nearly restoring intrathyroidal iodine stores.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
89
4
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 114 publications
(106 citation statements)
references
References 25 publications
9
89
4
3
Order By: Relevance
“…A wide range of neurointellectual disorders have been reported in school children from the area and attributed to various degrees of maternal thyroid insufficiency occurring during gestation (3, [15][16][17]. Based on this evidence, we set up a monitoring programme to track maternal thyroid function over the full course of gestation and, later on, a programme of iodine prophylaxis aimed at preventing/correcting any maternal thyroid insufficiency occurring during gestation in order to ultimately avoid neuro-behavioural and intellectual disorders in progeny was offered on a voluntary basis (18).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A wide range of neurointellectual disorders have been reported in school children from the area and attributed to various degrees of maternal thyroid insufficiency occurring during gestation (3, [15][16][17]. Based on this evidence, we set up a monitoring programme to track maternal thyroid function over the full course of gestation and, later on, a programme of iodine prophylaxis aimed at preventing/correcting any maternal thyroid insufficiency occurring during gestation in order to ultimately avoid neuro-behavioural and intellectual disorders in progeny was offered on a voluntary basis (18).…”
Section: Methodsmentioning
confidence: 99%
“…Thyroid function testing included serum free-thyroxine (FT 4 ) and TSH determinations. In assessing maternal thyroid function, we refer to both serum FT 4 and TSH internal trimester-specific reference intervals calculated in a cohort of consecutive longterm iodine-supplemented healthy anti-thyroperoxidase (TPO-Ab) antibody-negative pregnant women (18). At initial and final sampling TPO-Ab and anti-thyroglobulin (Tg-Ab) antibodies were also determined.…”
Section: Methodsmentioning
confidence: 99%
“…Nine RCTs (24,25,26,27,28,29,30,31,32) and eight observational studies (33,34,35,36,37,38,39,40) were included in the review. Seven RCTs were reported on the effects of maternal supplementation on maternal thyroid function (26,27,28,29,30,31,32,33,34,35,36,37,38,39,40). Of these, four RCTs also contained data on neonatal thyroid function (27,29,30,32).…”
Section: Study Selectionmentioning
confidence: 99%
“…It is also important to ensure an adequate supply of iodine during pregnancy for many reasons including optimizing the fetal thyroid stores, which are required for its normal start of function at 20 weeks, gestation (13,97). It has been unequivocally demonstrated that a good nutritional status of iodine, related to iodized salt, bread, and milk consumption over prolonged periods before pregnancy, can reduce the risk of TD during gestation (98,99). In populations with known iodine deficiency, supplementation with a minimum of 150-200 mg of iodine during pregnancy and lactation ensures the recommended intake is achieved.…”
Section: How and When Should All This Be Done?mentioning
confidence: 99%